Comparison of effectiveness of organized offences between two different championships in high level basketball - Mexas, K.; Tsitskaris, G.; Kyriakou, D.; Garefis, A. (International Journal of Performance Analysis in Sport, 2005)
The aim of the present study is to compare the offensive effectiveness of teams participating in high level basketball. The evaluation was established in relation to the type of defence, the position of the athlete initiating the offensive effort, the area by which the offence was released and the conditions under which the shot was attempted. The sample constituted of 25 games of the A1 Greek National Championship and 25 games of the European Championship. The results showed that offensive attacks from the region of the 3 present the higher rate of use and success. Man-to-man defence represents the most usual form of defence in modern European basketball, while the perimeter players are responsible for the majority of offensive efforts compared to the post players. The difference in effectiveness between national teams and basketball clubs were not statistically significant. The results demonstrate that the offensive effectiveness of Greek basketball clubs is equivalent to this played by the leading European national teams.